(untitled) (Research, Society and Development, 2020)
The insertion of the pharmacist in the multidisciplinary team aims to optimize the benefits and reduce the risks related to pharmacotherapy. The objective of this study was to describe the accomplishment of the bedside pharmaceutical follow-up for neonatal cardiac patients admitted to the Neonatal Intensive Care Unit, of a referral hospital in the state of Pará/Brazil. This is a descriptive study, with a quantitative approach, including all newborns hospitalized (19/100%), during the study period, with a closed diagnosis of congenital heart diseases, after the mother’s concession and signing the Term Free and Informed Consent. For the analysis of drug interaction and incompatibility, the following databases were included: Micromedex, Drugdex and Dinamed. The types of congenital heart disease presented were interventricular communication in 6 (31.57%) neonates and 3 (15.78%) presented Tetralogy of Fallot (T4F). Almost all neonates (17/89.47%) used drugs by continuous administration in an associated way. Of these, it was observed that 8 (42.10%) received drugs that interact with each other, negatively impacting the treatment. The pharmaceutical interventions carried out were change in the medication’s schedule with monitoring of possible adverse events. It is noteworthy that these actions were accepted by the service team and maintained until the medication was no longer needed and removed from the medical prescription. A computerized system, with information about the time of drug administration, could minimize pharmaceutical incompatibilities and drug interactions. It is concluded that the direct intervention of the pharmacist in the pharmacotherapeutic treatment of these patients becomes essential and can contribute to the sum of knowledge for their clinical improvement.